Effects of tungsten, chromium and zirconium on the corrosion behavior of ternary amorphous W–Cr–Zr alloys in 1 M NaOh solution - Aryal, Basu Ram; Bhattarai, Jagadeesh (Scientific World, 2011)
Simultaneous additions of tungsten, chromium and zirconium in the chromium- and zirconium-enriched sputter-deposited binary W-xCr and W-yZr are effective to improve the corrosion resistance property of the ternary amorphous W- xCr-yZr alloys after immersion for 240 h in 1 M NaOH solution open to air at 25°C. The corrosion rates of all the examined sputter-deposited (10-57)W-(18-42)Cr-(25-73)Zr alloys is higher than those of alloy-constituting elements (that is, tungsten, chromium and zirconium) in aggressive 1 M NaOH solution open to air at 25°C. The corrosion rates of all the examined sputter−deposited W–xCr–yZr alloys containing 10-57 at% tungsten, 18-42 at% chromium and 25-73 at% zirconium were in the range of 1.5-2.5 × 10−3 mm/y or lower which are more than two orders of magnitude lower than that of sputter-deposited tungsten and even about one order of magnitude lower than those of the sputter-deposited zirconium in 1 M NaOH solution. Keywords: Ternary W–Cr–Zr alloys; Amorphous; Corrosion rate; Open circuit potential; 1 M NaOH. DOI: http://dx.doi.org/10.3126/sw.v9i9.5516 SW 2011; 9(9): 39-43